Implementation of Standard Operating Procedures (SOP) in Improving Product Quality in Food Smes in Solok City - Fitri Suherini; Yohannes Simamora; Lusiana Lusiana (Jurnal Multidisiplin Sahombu, 2026)
This study aims to analyze the implementation of Standard Operating Procedures (SOPs) in improving product quality in food MSMEs in Solok City. The method used is a qualitative approach with data collection techniques in the form of observation, interviews, and documentation, which allows researchers to understand in depth how MSMEs implement SOPs in every stage of the production process, from raw material selection, processing, packaging, to product storage. The results of the study indicate that the implementation of SOPs has a significant impact on improving product quality, especially in terms of cleanliness, taste consistency, and presentation standards, resulting in more stable products and gaining consumer trust. Products produced by MSMEs in Solok City include cassava chips, fish dodol, typical Solok layer cake, and traditional drinks such as herbal medicine and local fruit syrup. Good implementation of SOPs also has an impact on increasing consumer satisfaction, expanding the market, and increasing trust in MSME products. However, the study found several obstacles, such as a lack of understanding among MSMEs regarding the importance of SOPs and limited human resources to implement procedures consistently. Therefore, ongoing training, outreach, and mentoring are needed so that MSMEs can implement SOPs optimally, so that product quality improves, consumers are more satisfied, and the development of MSME businesses in Solok City becomes more sustainable and competitive in local and regional markets.